Features of online sociological studies of risks of financial behavior of the population in the information and communication network Internet - M. Kibakin (Цифровая социология)
An overview of modern scientific concepts and accumulated scientific data for the development of digital sociology in terms of clarifying ideas about the features of the collection of primary sociological data has been presented. An importance of scientific understanding of the transformation of the content and specifics of the methodological tools of sociological research in the information and communication network Internet has been substantiated. The characteristic of the primary sociological information, contained in the Internet space and which is essential for the analysis of phenomena and processes in the course of conducting online research has been made. The classification has been substantiated, primary data groups have been distinguished according to the degree of openness, which include open, partially open and closed data. Separately, the characteristic of the obtained primary sociological data has been given by the method of technological access – analysis of blogs, the use of search engines for keywords, the inclusion of intelligent monitoring systems and analysis of social media, which are implemented either on stationary or mobile computer devices. The types of primary data on the format of communications have been adduced: advertising, network, vertically structured, horizontal, as well as the degree of reliability: “a sufficient level of reliability”, “doubtful information”, “unreliable information”. On the basis of the sociological research data, the features of collecting primary sociological information in the Internet space in the financial and economic sphere and identifying risks of the financial behavior of the population in the digital sphere have been shown. The qualitative and quantitative indicators of the use of Internet resources by young people for information, interaction, communication, training, business communication, entertainment and recreation, payment for goods and services have been presented. Conclusions about the need to take into account the specifics of the content and features of the study of primary sociological information in the digital space have been made.